2010
DOI: 10.1103/physrevb.82.113403
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in multiferroicBiFeO3nanodots: A first-principles-based study

Abstract: An effective Hamiltonian scheme is developed to investigate structural and magnetic properties of BiFeO 3 nanodots under short-circuit-like electrical boundary conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Among them, BiFeO 3 (BFO) is one of the most widely studied multiferroic materials, primarily because both its electrical and magnetic ordering occur above RT. In particular, multiferroic BFO nanostructures exhibit interesting magnetic and optical properties because of nanoscale size effects . So far, BFO nanomaterials with various sizes and shapes such as nanotubes, nanowires, nano/microcubes, nanospindles, and nanorods have been reported and exhibit different properties compared to the bulk form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, BiFeO 3 (BFO) is one of the most widely studied multiferroic materials, primarily because both its electrical and magnetic ordering occur above RT. In particular, multiferroic BFO nanostructures exhibit interesting magnetic and optical properties because of nanoscale size effects . So far, BFO nanomaterials with various sizes and shapes such as nanotubes, nanowires, nano/microcubes, nanospindles, and nanorods have been reported and exhibit different properties compared to the bulk form.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, multiferroic BFO nanostructures exhibit interesting magnetic and optical properties because of nanoscale size effects. [5][6][7][8] So far, BFO nanomaterials with various sizes and shapes such as nanotubes, 9 nanowires, 10,11 nano/microcubes, 12,13 nanospindles, 14 and nanorods 15 have been reported and exhibit different properties compared to the bulk form. Therefore, the design of multiferroic BFO nanostructures with novel and well-defined morphologies is important for both fundamental research and relevant for designing new multifunctional materials combining magnetic, ferroelectric, and optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a depolarizing electric field in finitesized ferroelectrics is known to reduce their Curie temperature and polarization P . There exists a critical size below which the nanoparticle ceases to be ferroelectric [24,25]. This effect was measured in free-standing BFO nanoparticles [19], where it was shown that P ≈ P Bulk for sizes down to 30 nm, with P reduced to 0.75P Bulk for size 13 nm.…”
Section: Introductionmentioning
confidence: 96%
“…These two ABO 3 perovskites are representatives of type I and type II multiferroics, respectively [3]. On the one hand, BiFeO 3 possesses simultaneously high magnetic transition temperature (about 640 K) and high FE Curie temperature T c (about 1,100 K) [4][5][6]. The polarization of TbMnO 3 *0.06 lC/cm 2 is much smaller than BiFeO 3 *100 lC/cm 2 by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 97%